Digitalization and taxation: Beware ad hoc measures - Alfons Weichenrieder (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
Digitalization expands the possibility for corporations to reduce taxes, mainly, but not exclusively, by allowing improved planning where profits can be shifted. Against this background, the European Commission and several countries emphatically demand and design new tax instruments. However, a selective turning away from internationally accepted principles of international taxation will bring up more questions than solutions. While there are good reasons to think about a fundamental regime switch in international corporate taxation, there are also good arguments for not turning to ad hoc measures that selectively target the relatively small market of Google and Facebook and raise only negligible tax revenues.
urn:nbn:de:hebis:30:3-456079
Keywords: 330; digitalization; taxation